2022
DOI: 10.1097/sih.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Standardized Patients for Practice in High Value Care

Abstract: IntroductionThis study examined the influence of high value care (HVC)-focused virtual standardized patients (VSPs) on learner attitudes toward cost-conscious care (CCC), performance on subsequent standardized patient (SP) encounters, and the correlation of VSP performance with educational outcomes.MethodAfter didactic sessions on HVC, third-year medical students participated in a randomized crossover design of simulation modalities consisting of 4 VSPs and 3 SPs. Surveys of attitudes toward CCC were administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A recent study by Bond et al 11 studied the use of VSPs for practice in high value care. The authors implemented and created VSPs as an additional opportunity for deliberate practice in novice learners.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Bond et al 11 studied the use of VSPs for practice in high value care. The authors implemented and created VSPs as an additional opportunity for deliberate practice in novice learners.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the education of medical students became hindered due to limited social interactions. Medical schools began utilizing virtual standardized patient encounters to mimic telehealth experiences in clinical practice to provide a different educational modality [ 14 ]. This allowed students to still have methods of practicing clinical skills while maintaining social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Often, studies have shown how hard it is to make valid, direct comparisons between AI-driven VPs and human SPS. For example, in one study [ 39 ] that used a randomized crossover design, medical students were taught about the delivery of high-value care to both kinds of patients. The investigators found that working with VPs seemed to preferentially enhance students’ skills for interviewing and delivering treatment.…”
Section: Reviewmentioning
confidence: 99%